(Tar)getting you: The use of online political targeted messages on Facebook. Issue 2 (July 2022) - Kruikemeier, Sanne; Vermeer, Susan; Metoui, Nadia; Dobber, Tom; Zarouali, Brahim
This study examines how mainstream political actors and other organizations use political targeted messages. For this purpose, a data set from ProPublica is used. The study examines 55, 918 sponsored Facebook ads that were posted by 236 political actors (i.e., political elites and other organizations) in the United States. (1) Topic classification was used to identify policy issues, (2) network analysis to identify the main policy issues from the various political actors, and (3) Sankey diagrams to visualize microtargeted messages. Our findings indicate that actors focus on traditionally owned issues (i.e., the Democratic Party: environmental policy, social issues, and social welfare; the Republican Party: foreign affairs, law, and government finances). No clear evidence for a focus on wedge issues can be found, however, some first indications (e.g., a focus on reproductive rights, LGBTQ+) are present in a targeted media environment. All in all, the current study helps us to understand in what way political actors deploy targeted messages.